What is the answer to -5f=-3(8-f)
2 answers:
Answer:
3
Step-by-step explanation:
to start this
you need to open the bracket, by multiplying -3(8-f)
we get
-5f = -3*8 -3 * (-f)
-5f = -24 + 3f
we collect like terms by taking f to where there is f so as to simplify our work
so we get
-5f -3f = -24
we get -3f because when a sign + or - crosses an equal sign, the sign changes that is. + changes to -, while - chnages to +
so add them
-8f = -24
minus (-) will cancel minus the we get
8f = 24
divide both side by 8
8f/8 = 24/8
f = 3
so f is = 3
Answer:
Step-by-step explanation:
-5f=-3(8-f)
Opening bracket
-5f = - 24 + 3f
Collecting like terms
-5f - 3f = -24
-8f = -24
Dividing by -8
f = -24/-8
f = 3
You might be interested in
Answer:
x = 9
-1 + 14x = 12x + 17
If you are trying to find the bigger angle, then the answer is A) Supplementary. But if you’re trying to find the small angle the answer is B) Complementary. C and D are both wrong.
Answer:
I think it’s either the first one or last.
Step-by-step explanation:
Answer:
32
Step-by-step explanation:
8/100 x 4
=
32/400